Automotive Industry, MICE, and Themed Special Event in Indonesia: A Qualitative Exploration - Della Novanty S.I.Kom; Irmawan Rahyadi, S.Sos., Mgr, Ph.D. (Syntax Idea)
This qualitative exploration delves into the Indonesia International Motor Show (IIMS), showcasing how thematic event management seamlessly intertwines with the dynamic automotive industry and the strategic principles of MICE (Meetings, Incentive, Convention, and Exhibition). IIMS, as a prime example, masterfully employs thematic event planning, creating immersive experiences for attendees while advancing broader organizational objectives. By aligning thematic principles with automotive showcases, IIMS highlights innovations and strengthens brand presence, all within the context of the influential MICE industry, underlining its role in fostering economic growth, knowledge exchange, and global collaboration. This study offers a holistic perspective on the synergy between special event management, the automotive sector, and MICE, providing valuable insights for event professionals and organizations seeking to excel in the art of creating memorable and impactful events.